Efficient Dynamic Nuclear Polarization at 800 MHz / 527 GHz with Trityl-nitroxide Biradicals - Mathies, Guinevere (Angew Chem Int Ed Engl, 2015)
Cross-effect (CE) dynamic nuclear polarization (DNP) is a rapidly developing technique that enhances the signal intensities in magic angle spinning (MAS) NMR spectra. We report CE DNP experiments at 211, 600 and 800 MHz using a new series of biradical polarizing agents referred to as TEMTriPols, in which a nitroxide (TEMPO) and a trityl radical are chemically tethered. The TEMTriPol molecule with the optimal performance yields a record (1)H NMR signal enhancement of 65 at 800 MHz at a concentration of 10 mM in a glycerol/water solvent matrix. The CE DNP enhancement for the TEMTriPol biradicals does not decrease as the magnetic field is increased in the manner usually observed for bis-nitroxides. Instead, the relatively strong exchange interaction between the trityl and nitroxide moieties determines the magnetic field at which the optimum enhancement is observed.